Definition of Guideline-Based Metrics to Evaluate AAL Ecosystem's Usability. (14th November 2022) - Romeiro, Carlos; Araújo, Pedro
Abstract : The elderly population growth has posed several challenges which the current healthcare systems are incapable of handling. In the past few years, there has been a close collaboration between both the scientific and industry communities to provide feasible solutions capable of addressing the growing demands from people with special needs, namely, in terms of assistance and improvement of their overall life quality, which promoted to the development of the ambient assisted living (AAL). Despite the general consensus regarding its positive impact in the user's daily life, several challenges compromise their overall adoption. As a consequence, the research undertaken so far focused over the mitigation of technical-related limitations, overshadowing user-related limitations, namely, the ecosystem's usability. This article presents a parametrization of the literature guidelines, which provides the end-users a consistent and accurate way of using the heuristic methodology to assert the interface's usability without relying in external entities with specialized know-how.